2003
DOI: 10.1029/2003jd003552
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of O3 formation in the Houston urban and industrial plumes during the 2000 Texas Air Quality Study

Abstract: [1] Ozone formation in the Houston area during a period of high ozone concentrations that occurred on 29 August 2000 during the TexAQS 2000 study is examined to understand differences in the sources of O 3 precursors and the rate and efficiency of ozone formation over the city of Houston and the industrialized Ship Channel region to the east of Houston. From late morning through late afternoon on 29 August, a period of stagnation occurred, allowing accumulation of O 3 and product species separately over downto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 16 publications
8
93
2
1
Order By: Relevance
“…To further support this, we plot the daily OPE x versus the peak of NO x in early morning ([NO x ] 0 , a surrogate of NO x emissions from local traffic) in Figure 8. Similar to that reported by Chou et al [2009] Dommen et al, 1999;Ge et al, 2012;Kleinman et al, 2000;Nunnermacker et al, 1998;Olszyna et al, 1994] [Chou et al, 2009] and also in agreement with those at various urban sites, e.g., Houston and Tennessee, USA [Daum et al, 2003;Zaveri et al, 2003]. However, the correlation between OPE x and [NO z ]/[NO y ] is contrary to that observed at a rural site (SDZ) in Beijing, where~75% of O 3 pollution is from regional transport rather than local photochemical production [Ge et al, 2012].…”
Section: Ozone Production Efficiency (Ope X )contrasting
confidence: 51%
“…To further support this, we plot the daily OPE x versus the peak of NO x in early morning ([NO x ] 0 , a surrogate of NO x emissions from local traffic) in Figure 8. Similar to that reported by Chou et al [2009] Dommen et al, 1999;Ge et al, 2012;Kleinman et al, 2000;Nunnermacker et al, 1998;Olszyna et al, 1994] [Chou et al, 2009] and also in agreement with those at various urban sites, e.g., Houston and Tennessee, USA [Daum et al, 2003;Zaveri et al, 2003]. However, the correlation between OPE x and [NO z ]/[NO y ] is contrary to that observed at a rural site (SDZ) in Beijing, where~75% of O 3 pollution is from regional transport rather than local photochemical production [Ge et al, 2012].…”
Section: Ozone Production Efficiency (Ope X )contrasting
confidence: 51%
“…Beginning with measurements done in 2000, it had been observed that ratios of hydrocarbons to NO x in industrial plumes were consistently factors of 2-15, and in some isolated instances even a factor of 50 or higher, than the ratios reported in the inventories (Daum et al, 2001). Ratios of hydrocarbon to NO x , higher than those in bottom-up emission inventories, were observed for alkanes, alkenes, and aromatics, but overall atmospheric reactivity was dominated by alkenes (Daum et al, 2003;Ryerson et al, 2003). These findings led to multiple years of efforts to identify the sources of the missing or underestimated emissions.…”
Section: Zavala Et Al 2015amentioning
confidence: 99%
“…Rapid ozone (O 3 ) formation processes are associated with releases of highly reactive volatile organic compounds (HRVOCs) from industrial facilities predominantly located in Houston's Ship Channel (HSC), which comprises large agglomerations of petrochemical industries (Kleinman et al, 2002;Daum et al, 2003Daum et al, , 2004Ryerson et al, 2003;Berkowitz et al, 2005); the impact of non methane hydrocarbons on downwind non-industrialized areas has been extensively studied . Among HRVOCs compounds that serve as radical sources are of particular concern.…”
Section: Introductionmentioning
confidence: 99%